Penguatan Pemberdayaan Masyarakat sebagai instrument Pengembangan Pariwisata Berkelanjutan: Kasus Cagar Alam Tangkoko di Indonesia - Bet El Silisna El Silisna Lagarense (HOSPITALITI DAN PARIWISATA, 2018)
One of the main principles a community empowerment in sustainable development is that the primary benefits should be returned to the local community and become an integral part of the development activity. However, Tangkoko as a centre for natural tourism development in North Sulawesi, Indonesia has tended to concentrate on tourism development without adequately considering livelihoods of local communities. This study is aimed to examine to what extend The model of community empowerment can be applied into the practice of community empowerment development in Tangkoko Nature Reserve. The study will contribute to the formulation of government policy in formulating and establishing the R- Urban conservation efforts, especially in the utilization of local natural resources by using the principles of sustainable development in Tangkoko Nature Reserve. In addition, the results of the study will be able to promote the use of community-based empowerment and participation through the use high-value natural surrounding environment. This study involves desktop research and fieldwork comprising questionnaire surveys and on-site observations to provide evidences of community-based empowerment in Tangkoko Natural Reserve. This study develops a model of sustainable tourism development through creative community empowerment that will ensure the outcomes from tourism will be returned to strengthen the local economy as well the quality of life of local communities.